2005
DOI: 10.1116/1.2049307
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium diboride thin films by chemical vapor deposition from a single source precursor

Abstract: High quality, stoichiometric thin films of hafnium diboride are deposited by chemical vapor deposition from the precursor Hf͓BH 4 ͔ 4 at deposition temperatures as low as 200°C. An activation energy of 0.43 eV͑41 kJ/ mol͒ is obtained for the overall process as monitored by temperature programmed reaction studies. Films deposited at low temperatures ͑Ͻ500°C͒ are structurally amorphous to x-ray diffraction; a 12 nm thick film is sufficient to prevent copper diffusion into silicon during a 600°C anneal for 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 37 publications
3
87
0
1
Order By: Relevance
“…Hu et al [21] observed the presence of Si on the top of epitaxial ZrB 2 films grown at similar temperatures. We previously demonstrated that there is a reaction barrier for the precursor Hf(BH 4 ) 4 to react with a fresh silicon surface [14]; here, we interpret that Si diffuses to the film surface at high growth temperatures and reduces the precursor reaction probability or otherwise interferes with HfB 2 growth. The low growth rate and the high silicon diffusivity are potential problems for using MB 2 films as buffer layers for growing GaN epitaxially on Si, especially because Si is a dopant in GaN [23].…”
Section: Texture Of Hfb 2 Films Grown On Single-crystal Substratesmentioning
confidence: 86%
See 2 more Smart Citations
“…Hu et al [21] observed the presence of Si on the top of epitaxial ZrB 2 films grown at similar temperatures. We previously demonstrated that there is a reaction barrier for the precursor Hf(BH 4 ) 4 to react with a fresh silicon surface [14]; here, we interpret that Si diffuses to the film surface at high growth temperatures and reduces the precursor reaction probability or otherwise interferes with HfB 2 growth. The low growth rate and the high silicon diffusivity are potential problems for using MB 2 films as buffer layers for growing GaN epitaxially on Si, especially because Si is a dopant in GaN [23].…”
Section: Texture Of Hfb 2 Films Grown On Single-crystal Substratesmentioning
confidence: 86%
“…The deposition system and the growth procedure are described in detail elsewhere [14]. Unless specified, films were grown with a fixed precursor feed rate of 3.2 Â 10 16 molecules/s, for which the precursor partial pressure is estimated to be 10 À5 À10 À6 Torr inside the chamber; films were grown to $300 nm thick by controlling the growth time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A static CVD system, operating at high precursor pressures (15 Torr), was built to achieve conformal coatings on silica colloidal crystal templates. Hafnium borohydride (solid at room temperatures with a 15-Torr vapour pressure) was used as a single source precursor for HfB 2 CVD and was prepared in an inert atmosphere 36,41,42 . Equipment needed for the static CVD included a rough vacuum pump, ultra high purity argon, tube furnace, two glass tubes (0.75 inches in diameter connected by an on/off valve with ground glass joints).…”
Section: Methodsmentioning
confidence: 99%
“…42 The substrate is heated radiatively with a tungsten filament; the substrate temperature is measured with a K-type thermocouple clamped on top of the mounting platen. A reference thermocouple at the back of heating stage is also used to monitor the temperature.…”
Section: Ecs Journal Of Solid State Science and Technology 3 (5) Q79mentioning
confidence: 99%